Ship wake forcing and performance of a living shoreline segment on an estuarine shoreline - Everett, Cassandra L.; Williams, Oscar; Ruggiero, Emma; Larner, Michael; Schaefer, Rachel; Malej, Matt; Shi, Fengyan; Bruck, Jules; Puleo, Jack A. (Frontiers in Built Environment, 2022)
Investigation of the effectiveness of Natural and Nature-Based Features (NNBF) for protecting shorelines from ship wake is increasingly important with continued development along the coast, especially when combined with sea level rise. Studies that investigate the wave energy dissipation capacity of different techniques and account for variation in context will lead to improvements and innovation in designed NNBF. Few studies have examined the performance of NNBF in protecting shorelines from ship wake. In this study of a low-sloping estuarine shoreline adjacent to a major shipping route, a natural design using coir logs and wooden staking was implemented in a T-head groin configuration. Pressure transducers and electromagnetic current meters were deployed over ~1.5 months to investigate the energy dissipation and velocity attenuation capabilities of the installation. Results indicate that ship wakes account for 25 - 50% of the total daily energy impacting the shoreline at the study site. Peak background velocities are typically over 50% smaller than the largest ship wake velocities. Field data and results of the fully nonlinear Boussinesq model, FUNWAVE-TVD, indicate that the installation is capable of decreasing energy impacting the shoreline by 10 - 80%, reducing shore normal velocities by 20 - 33%, and is effective over the lower 50% of the tidal range and when submerged up to twice its height. Elevation surveys of the site indicate accrual of sediment within the installation, suggesting wave diffraction patterns promoting further accretion at the site over time. Observations indicate that coir logs may be effective in reducing wave energy from ship wakes but may fail under storm conditions in a moderate fetch confined channel. Findings from this study illustrate the opportunities and challenges nature-based solutions face in addressing ship wakes, and their ability to protect shorelines under high energy stressors